Desarrollo de la conciencia fonológica del lenguaje para lograr aprendizaje en la lecto-escritura en los niños y niñas de preparatoria primer grado de educación general básica de la escuela “Ciudad De Zumba” en el periodo lectivo 2013-2014 - Ochoa Jaramillo, Johanna Soledad (2015)
This thesis refers to: Development of phonological awareness LANGUAGE LEARNING TO ACHIEVE IN LITERACY IN CHILDREN OF HIGH GRADE GENERAL BASIC EDUCATION SCHOOL "CIUDAD DE ZUMBA" IN THE SEMESTER 2013-2014. So I raised the following debriefing ¿how aid the development of phonological awareness of language in the learning of literacy in children of the first year of basic education of the school "Ciudad de Zumba" in the period of the academic year 2013-2014? The following study is focused on the development of phonological awareness in children of school first grade of basic general education "Ciudad de Zumba" school, as this is essential for learning to read and write basis, therefore, it has seen the need for researching in this area, to know the reality of education in preschool, with phonological awareness have a skill that children to develop to recognize phonemes with their respective grapheme. Previously the General Purpose formulated: Educate teachers about the importance ranging from pre-development of phonological awareness of language learning to achieve literacy in children from the first grade of elementary school “Ciudad de Zumba" Canton Chinchipe Province Zamora. The methods used were: scientific, inductive, deductive, analytical, synthetic and descriptive that helped to follow step by step the investigation; techniques applied were: the survey that applied it to the teachers to identify the development of phonological awareness of language learning to achieve literacy In the implementation of the survey concluded that: 100% of the teachers recognize that the development of phonological awareness of language learning can achieve literacy in school children. From the results of the observation guide concludes that 15% satisfactory: phonologically. Listen and running calligraphic traits and 20% Unsatisfactory on: Joins points according to phonological vocal masterpiece.